Odpowiedź :
Odpowiedź:
1. Zapisz w postaci sumy:
a)
2 · (5x + y – 3z) = 10x + 2y - 6z
b)
2x · (3x – 2y + 4z) = 6x² - 4xy + 8xz
c)
(15x + 10y - 25z) : (-5) = -3x - 2y + 5z
2.
Przekształć wyrażenie na sumę i zredukuj wyrazy podobne:
a)
-3 · (4x – 3y) + 4 · (x – 2y) = -12x + 9y + 4x - 8y = -8x + y
b)
2x · (x – 3) – (5x2 + 3x) = 2x² - 6x - 5x² - 3x = -3x² - 9x
c)
3 · (x + 2y – 4) - 2 · (3 - 4y + 2x) = 3x + 6y - 12 - 6 +8y - 4x = -x + 14y - 18
Szczegółowe wyjaśnienie:
Odpowiedź:
1
a) 10x+2y-6z
b) 6x-4xy+8xz
c) -3x+(-2y)+5z
2
a)-12x+9y+4x-8y=-8x+y
b)2[tex]x^2[/tex]-6x-5[tex]x^2[/tex]-3x=-3[tex]x^2[/tex]-9x
c)3x+6y-12-6+8y-4x=-x+14y-18